2019
DOI: 10.1002/star.201800351
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Postprandial Blood Sugar Response Estimated by Enzymatic Kinetics of In Vitro Digestive and Fine Molecular Structure ofArtocarpus heterophyllusLam Seed Starch and Several Staple Crop Starches

Abstract: Experimental investigation of molecular structure, pasting properties, and post‐prandial blood sugar (PPBS) is performed using the kinetics of in vitro starch hydrolysis on jackfruit seed starch (JFSS), cassava starch (CS), potato starch (PS), maize starch (MS), wheat starch (WS), and rice starch (RS). The results show that JFSS displays smaller and smoother granule morphology, a higher amylose content (27.01%), a greater proportion of B3+ chains (12.83%), and a lower proportion of B1 chains (36.08%) than CS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
(97 reference statements)
2
9
0
Order By: Relevance
“…Similarly, Faraj et al ( 18 ) showed that the degree of damage to the extrudate granule morphology of different types of barley flour significantly differed. Moreover, the EJFSS, ECS, EPS, and EWS granule morphology exhibited numerous large emulsion bumps with concave holes ( Figure 2 ), in contrast to the smoother, smaller, and round or bell-shaped native starch granule surfaces observed previously ( 4 ). Thus, the extrudate granules may have been seriously damaged after IEMS treatment, leading to superior digestibility compared to that of their raw starches ( 28 ).…”
Section: Resultsmentioning
confidence: 64%
See 4 more Smart Citations
“…Similarly, Faraj et al ( 18 ) showed that the degree of damage to the extrudate granule morphology of different types of barley flour significantly differed. Moreover, the EJFSS, ECS, EPS, and EWS granule morphology exhibited numerous large emulsion bumps with concave holes ( Figure 2 ), in contrast to the smoother, smaller, and round or bell-shaped native starch granule surfaces observed previously ( 4 ). Thus, the extrudate granules may have been seriously damaged after IEMS treatment, leading to superior digestibility compared to that of their raw starches ( 28 ).…”
Section: Resultsmentioning
confidence: 64%
“…This may lead to improved digestibility of starch samples after extrusion cooking. In addition, based on Li et al ( 4 ), the different conversion abilities of nutrition fragments between JFSS and potato starch compared to other kinds of starch, may be related to the higher amylose content in JFSS (27.01%) and potato starch (24.82%) than in the other starch samples (3.25–21.65%). This led to higher formation of nearly perfect crystals and better short-range order structures for JFSS and potato starch, resulting in different levels of digestibility after extrusion.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations